Prognostic significance of non-thyroidal illness syndrome in sepsis - N. Krishna Geetha; K.I.S.N Vaishnavi; Kakumani Jagadeswar; A. Gowri Shankar (Romanian Journal of Infectious Diseases)
Background and objectives. Sepsis is a common diagnosis among ICU patients. Therefore, the present study aimed at assessing the prognostic significance of non-thyroidal illness syndrome (NTIS) in sepsis. Materials and methods. The study was done as a retrospective analysis on adult patients of age greater than 18 years who were admitted with sepsis to an urban tertiary care ICU at Saveetha Medical College and Hospital. Results. The study found that NTIS can manifest as a fall in T3 alone, T4 alone, or both T3 and T4. A combined fall in T3 and T4 strongly correlates with poor primary outcomes (28-day mortality) compared to a fall in either hormone alone. Advancing age in septic patients leads to a greater combined fall in T3 and T4 values and an increased mortality rate, especially among females. The overall mortality rate in this series was 55%, with severe infections and high APACHE II scores contributing to lower hormone levels and higher severity. Conclusion. NTIS should be considered an indicator of poor prognosis in septic patients, necessitating aggressive management. It underscores the importance of assessing TSH alongside T3 and T4 in critically ill patients, although treating NTIS was beyond the scope of this study.